Opening Address Opening Ceremony Leadxucs 2025: Accelerator of Excellent Students / Prof. Dr Mohd Hafiz Mohd Hanafiah - Mohd Hanafiah, Mohd Hafiz (2025)
Thus, LEADxUCS 2025 programme is designed with this reality in mind, bringing together UiTM alumni and leading industry partners such as Sunway Group, TalentCorp, and Boustead Hotels & Resorts Sdn. Bhd., to share their knowledge and experience through impactful modules including Executive Grooming, Boardroom Communication, Critical Thinking, and Leadership Pitching